(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
This research aims to develop and empirically validate a methodological approach for assessing the impact of digitalization on business process economic efficiency and determining the optimal level of digital transformation investment. The study employs a mixed-methods approach combining quantitative analysis of data from 47 Ukrainian enterprises across manufacturing, retail, and service sectors with expert evaluations. An Integrated Digitalization Maturity (IDM) indicator was developed with industry-specific weighted coefficients for various digital technologies. The research established statistically significant correlations between the IDM indicator and key economic performance metrics: return on sales (r=0.723), labor productivity (r=0.684), and asset turnover (r=0.512), with correlation strength varying by industry (strongest in services at r=0.78). A one-unit increase in digital maturity corresponds to an average 2.94 percentage point increase in sales profitability. The research introduces a novel integrated approach to assessing digital maturity that accounts for industry specifics and enterprise scale. The developed economic-mathematical model addresses the non-linear relationship between digital investments and economic returns, determining optimal digitalization levels of 3.75 for manufacturing, 3.92 for retail, and 3.84 for service enterprises. The digital initiatives prioritization matrix classifying technologies into "quick wins," "strategic projects," "infrastructure projects," and "low-priority initiatives" provides practical guidance, enabling enterprises to optimize digital transformation investments based on quantifiable economic criteria rather than technological trends alone.